New York Scholastic - Putting it in writing Scholastic guides Steve Otfinoski (144 p ill, 1993)
Provides examples, models, and advice for writing letters to friends, relatives, and businesses, or for preparing school reports
Hurg
5
Keywords: English language -- Composition and exercises -- Juvenile literature; Letter writing -- Juvenile literature